Efektivitas Bimbingan Kelompok Berbasis Manajemen Waktu untuk Mengurangi Perilaku Kurangnya Kedisiplinan Waktu di SMK - Tari Datu Lapik; Leni Lewi Pongdatu; Selviana Sattu; Monika Tandililing (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
This study aims to assess the effectiveness of time management-based group guidance services in reducing time-disciplined behavior among vocational high school students. The study used a qualitative approach with a case study design, involving several students with a history of tardiness and undisciplined time management at school. Data were collected through participant observation, structured in-depth interviews, and documentation of time planning and daily activity diaries during the group guidance sessions. Data analysis was conducted through data reduction, data presentation, and drawing conclusions using thematic analysis techniques. The results indicate that time management-based group guidance positively impacts students' awareness of the importance of time discipline, changes in habitual patterns, and improves their ability to plan and organize daily activities. Students reported that time management techniques, the use of daily schedules, and weekly reflections helped them reduce tardiness and procrastination. Some students also experienced increased regularity in completing schoolwork and active participation in extracurricular activities. The conclusions of this study indicate that time management-based group guidance is an effective service in the vocational high school context for reducing time-disciplined behavior if it is delivered systematically, sustainably, and takes into account student characteristics. The practical implication for guidance and counseling services is the need to develop a time management group guidance module based on the local context of schools and students.